Ore genesis of the Xa Loi gold deposit, Central Vietnam: evidence from S–O–H isotopes and fluid inclusion compositions - Ngo Xuan, Dac; Trinh Hai, Son; Bui The, Anh; To Xuan, Ban; Cao Viet, Anh (Vietnam Journal of Earth Sciences, 2025)
The Xa Loi gold deposit, located within the Truong Son Fold Belt of central Vietnam, provides a critical case study for understanding magmatic-hydrothermal gold systems in Southeast Asia. This study integrates sulfur (δ³⁴S), oxygen-hydrogen (δ¹⁸O–δD) isotopes, microthermometry, and stepwise-crushing gas-inclusion analyses to constrain the origin, evolution, and physicochemical conditions of the ore-forming fluid. Pyrite exhibits a narrow δ³⁴S range from –0.49‰ to +2.90‰, indicating a homogeneous sulfur source derived from magmatic degassing under moderately oxidizing conditions. Quartz δ¹⁸O and fluid δD values plot entirely within global magmatic fields, demonstrating that the aqueous component of the hydrothermal system was sourced from a deep, evolved felsic-intermediate magma with no meteoric contribution. Fluid-inclusion gases define a H₂O–CO₂–N₂–CH₄ system characterized by CO₂/CH₄ > 1 and elevated N₂/Ar ratios (≈400–1100), with all data plotting within the Magmatic-Evolved Magmatic fields of the CO₂/CH₄–N₂/Ar diagram. These signatures indicate a CO₂-rich, moderately oxidized magmatic fluid that underwent limited interaction with N-bearing crustal rocks during ascent. The progressive transition from SFI to Mixing and PFI inclusion populations records increasing oxidation consistent with magmatic degassing. Collectively, the S–O–H isotope systematics and gas compositions reveal that the Xa Loi gold deposit was formed by a magmatic-dominated hybrid fluid, in which sulfur, water, CO₂, and the conditions required for Au transport were supplied directly by an evolved magma and only slightly modified by crustal interaction. This genetic model highlights the role of deep magmatic processes in the formation of gold deposits along the Truong Son Fold Belt.